KONSTRUKSI KEASPEKAN IMPERFEKTIF PROGRESIFBAHASA KODI, SUMBA BARAT DAYA - Sukerti, Gusti Nyoman Ayu; Artawa, Ketut; Satyawati, Made Sri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 22 (2015): September 2015, 2016)
Kodi language falls into a category of head-marking language and its predicate is attached by pronominal clitic consisting of information on morphological cases. Pronominal clitic has two different forms namely proclitic and enclitic which cross-reference with the core arguments of predicate. Aspectual construction requires a specific form of aspectual clitic which shows an agreement with the type and number of person or noun phrase in the subject slot.Imperfective aspect construction marked by progressive marker tengera triggers the existence of aspectual clitic cross-referencing to subject argument. In addition to canonical construction of SVO, this imperfective construction can also be seen in a marked construction. The marked construction is syntactically signified by aspectual clitic attached to a host (PRED) while pronominal clitic in the form of genitive case is attached to the imperfective marker tengera. This marker gives information about internal and temporal structure of a particular situation without a reference to other aspects. Aspectual feature is a part of the nuclear operators which have scope over the nucleus. It modifies the action, event or state itself without reference to the participants.
Keywords: Kodi language, imperfective aspect, aspectual clitic, and Role and Reference Grammar